Pemberian Edukasi Berbasis Multimedia dalam Meningkatkan Kualitas Persiapan Usus pada Pasien Kolonoskopi - Anatha C Selaindoong; Agung Waluyo; Riri Maria (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effectiveness of multimedia-based education in improving the quality of bowel preparation in patients undergoing colonoscopy. The method used is a systematic review of the literature using PRISMA diagrams based on the PICO format. In October 2022, article searches were conducted using four web databases. The study results showed that five articles matched the researchers' aims and were analyzed further. These five articles examined the effectiveness of multimedia-based education in colonoscopy patients and obtained a positive effect on improving the quality of bowel preparation in colonoscopy patients. In conclusion, multimedia-based education is recommended as an educational method for bowel preparation for patients who will undergo colonoscopy to increase the quality of bowel preparation. Keywords: Multimedia Education, Colonoscopy, Bowel Preparation